2020
DOI: 10.3233/jhd-190377
|View full text |Cite
|
Sign up to set email alerts
|

The Ripple Effect: A Qualitative Overview of Challenges When Growing Up in Families Affected by Huntington’s Disease

Abstract: Background: The average age for the onset of Huntington's disease (HD) is an age when many people have children and caretaking responsibilities; HD is therefore likely to impact the whole family, including children and adolescents. Despite an increased understanding of the challenges for young people of growing up in a family affected by HD, a continuing lack of available knowledge has led to inadequate youth-focused support in many countries. Objective: This study explored the risks of growing up in a family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…By considering the mutation status, other people (e.g., potential romantic partners) could also strongly influence the participants’ important life choices, such as in the area of education or in having children. Recent research supports the idea that young people's experiences of HD depend on a range of factors similar to those in the socio‐ecological framework (Kjoelaas et al, 2020). The findings highlight the need to evaluate the process of undergoing the test for HD not only as a personal choice but also as a lifelong process that is continuously influenced by a number of variables proximal and distant to an individual.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…By considering the mutation status, other people (e.g., potential romantic partners) could also strongly influence the participants’ important life choices, such as in the area of education or in having children. Recent research supports the idea that young people's experiences of HD depend on a range of factors similar to those in the socio‐ecological framework (Kjoelaas et al, 2020). The findings highlight the need to evaluate the process of undergoing the test for HD not only as a personal choice but also as a lifelong process that is continuously influenced by a number of variables proximal and distant to an individual.…”
Section: Discussionmentioning
confidence: 55%
“…By considering the mutation status, other people (e.g., potential romantic partners) could also strongly influence the participants' important life choices, such as in the area of education or in having children. Recent research supports the idea that young people's experiences of HD depend on a range of factors similar to those in the socio-ecological framework (Kjoelaas et al, 2020…”
Section: Socio-ecological Frameworkmentioning
confidence: 64%
See 1 more Smart Citation
“…This study explored ACEs of individuals who grew up with a parent with HD. Previous studies suggest that these young people can be exposed to several negative life events and challenging tasks (Kjoelaas et al, 2020;van der Meer et al, 2012). However, this is the first study to provide an in-depth exploration of this group's exposure to ACEs and the relationship between caregiver support and adversity.…”
Section: Discussionmentioning
confidence: 87%
“…Research has also suggested that children who grow up with a parent with HD often do not receive adequate support or help and are left with overwhelming responsibilities at home (e.g. Dondanville et al, 2019;Kjoelaas et al, 2020;Lewit-Mendes et al, 2018). To date, only one study has systematically explored the presence of adverse childhood experiences in relation to HD, indicating that this group of children experiences significantly more adversities, such as domestic violence and parental dysfunction, than children growing up with parents with another inheritable genetic disease (van der Meer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%